2006
DOI: 10.1093/pasj/58.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Periodic Oscillations of Microwave Emission in Solar Active Regions

Abstract: In this paper we discuss QPOs registered at microwaves using the Nobeyama Radioheliograph (NoRH). Our main conclusions concerning the QPO, found from NoRH observations, include: In addition to widely known 3-min oscillations and comparatively less investigated shorter fluctuations, we have registered over sunspots at microwave range also a diversity of more long-term periodic processes having typical periods of tens and hundreds of minutes. In some sunspots these periods are dominating. In a single active regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 14 publications
0
20
0
5
Order By: Relevance
“…In microwave emission above sunspots, oscillations of tens and hundreds of minutes have been detected (Gelfreikh et al 2006;Chorley et al 2010) with the Nobeyama Radioheliograph (NoRH, Nakajima et al 1994). In particular, Chorley et al (2010) indicated the presence of two periodicities in each analysed sunspot.…”
Section: Introductionmentioning
confidence: 99%
“…In microwave emission above sunspots, oscillations of tens and hundreds of minutes have been detected (Gelfreikh et al 2006;Chorley et al 2010) with the Nobeyama Radioheliograph (NoRH, Nakajima et al 1994). In particular, Chorley et al (2010) indicated the presence of two periodicities in each analysed sunspot.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 30-60 min oscillations have been detected in the intensity difference of two solar radio signals recorded at two close frequencies, 9.67 GHz and 9.87 GHz (Kobrin & Korshunov 1972). Oscillation periods of tens and hundreds of minutes have also been seen as modulation of the microwave emission (Gelfreikh et al 2006). Recently, oscillations of the line-of-sight velocity with periods from 60 to 80 min have been detected in sunspots (Efremov et al 2009) in the Doppler shift of lines in the sunspot spectrum formed at different heights.…”
Section: Introductionmentioning
confidence: 99%
“…The quasi-periodic oscillations are registered practically in all wavelength ranges and in all structures of the solar atmosphere (Bogdan 2000, Fludra 2001, Gelfreikh, Nagovitsyn & Nagovitsyna 2006. Oscillations have periods from seconds to hours or even days.…”
Section: Introductionmentioning
confidence: 93%